2010
DOI: 10.1021/nn100116y
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Supramolecular Architectures Self-Assembled on Metal Surfaces

Abstract: We report the controllability of the complexity of surface-supported supramolecular assembly on metal surfaces. By introducing mismatch between the molecular packing and the surface atomic periodicity in the systems with comparable strength of intermolecular and molecule-substrate interactions, a homomolecular assembly exhibiting two-dimensional multilevel structures up to quaternary level was observed. In such a multiperiodicity modulated system, neither the intermolecular nor molecule-substrate interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…The images have many features which are not clearly assigned, but a reasonable assumption would be that the disordered regions consist of solvent from the pulse deposition, 29,30 as well as molecules with orientations in which the molecular axis is tilted away from the surface normal. 25,31 In order to characterize the internal structure of the hexamers, the position of each molecule within the hexamer relative to the cluster centroid was recorded for each clearly and completely resolved hexamer in the images. These positions were sorted by the chiral conformations (labeled "S" and "Z"), when that assignment was possible, then averaged.…”
Section: Resultsmentioning
confidence: 99%
“…The images have many features which are not clearly assigned, but a reasonable assumption would be that the disordered regions consist of solvent from the pulse deposition, 29,30 as well as molecules with orientations in which the molecular axis is tilted away from the surface normal. 25,31 In order to characterize the internal structure of the hexamers, the position of each molecule within the hexamer relative to the cluster centroid was recorded for each clearly and completely resolved hexamer in the images. These positions were sorted by the chiral conformations (labeled "S" and "Z"), when that assignment was possible, then averaged.…”
Section: Resultsmentioning
confidence: 99%
“…molecular nanostructures through controlling the adsorption and assembly process of functional molecules at the solid/liquid interface. [9][10][11][12][13] The rapid development of surface characterization techniques in the past few decades has greatly facilitated the study of the solid/liquid interface. Among many techniques, scanning tunneling microscopy (STM) is a powerful tool to observe, analyze, and control the molecular adlayers under different conditions (ambient, UHV, liquid/solid interface) on substrates at atomic or submolecular resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of bulk ferrocene have found that the Cp rings of ferrocene prefer to pack perpendicular to one another, with the hydrogens of the Cp ring adjacent to the Fe center of the neighboring ferrocene. [59][60][61] We do not see the DFA packing perpendicular to one another, but an underlying benzene monolayer may stabilize the DFA causing it to physisorb in a specific manner.…”
Section: Resultsmentioning
confidence: 75%
“…[31][32][33] A study by Zhong et al has reported ferrocene attached to organic chains that adsorb on Cu(110) with the ferrocenyl group in both orientations, and even switching orientation from parallel to perpendicular between scans with a scanning tunneling microscope (STM). 34 It has been reported that ferrocene dissociates when physisorbed to Au(111) at room temperature. 35 Lowtemperature STM studies show that ferrocene nondissociateively physisorbs to a Cu(111) surface.…”
mentioning
confidence: 99%